Комплексная оценка состояния канала связи и обобщенного критерия живучести - Головкина, Л. В.; Борисенко, А. С. (НТУ "ХПИ", 2015)
Предложено определение обобщенного критерия живучести в беспроводной сенсорной ZigBee сети с ячеистой топологией при разрушающих действиях и учетом состояния реального канала связи, условной надежности узлов. Задача определения живучести сети сведена к задаче связности графа. Изменения структуры сети в результате разрушающих действий учтены в виде изменения графовой модели. Сделаны выводы о методах маршрутизации, которые используются в оценке состояния канала связи в сети.

Determination of the generalized criterion of vitality is offered in the wireless sensory ZigBee network with mesh topology at destroying actions and account of the state of the real communication channel, conditional reliability of knots. The task of determination of vitality of network is taken to the task of connections of graph. Changes of network structure as a result of destroying actions take into account as the change of graph model. Importance of routing data is confirmed in estimation of quality of communication channel both in the case of destruction of 3 and 6 ribs on the basis of calculations and measurings conducted with the real modules of XBee-PRO. The conclusions about methods routing which are used in estimation of the state of communication channel in a network.
Complex estimation of the state of communication channel and generalized criterion of vitality
Keywords: условная надежность узлов; граф; разрушающие действия; graph; destroying actions